Biological soil crust succession in deserts through a 59-year-long case study in China: How induced biological soil crust strategy accelerates desertification reversal from decades to years. (February 2020) - Deng, Songqiang; Zhang, Dayi; Wang, Gaohong; Zhou, Xiangjun; Ye, Chaoran; Fu, Taoran; Ke, Tan; Zhang, Yurui; Liu, Yongding; Chen, Lanzhou
Abstract: The regeneration of induced biological soil crusts (IBSCs) is regarded as an effective strategy for combating desertification. Three types of BSCs, namely, cyanobacterial, lichen and moss, are well-accepted as the main succession phases and are hypothesized to represent a continuous process. Herein, natural BSCs (NBSCs) and IBSCs with accurate ages from a 59-year-long field study were investigated to understand the entire BSC succession process. Shifts in nutrient levels, microbial composition and ecological functions suggested that cyanobacterial inoculation successfully accelerated BSC succession from decades to years by promoting the microbial multifunctions related to carbon and nitrogen fixation. The four state transitions of the BSC community accompanied by the turn-over of carbon and nitrogen fixators provide clues to the factors restricting the recovery process and climax of arid ecosystems. This study provides the first description of the continuous BSC succession, comprehensively discusses the mechanisms of BSC formation and succession and provides important guides for selection of strategies for the engineering reversals of desertification. Highlights: First long-term (59-year) field experiment on BSC formation and development. First evidence proving the continuous succession process of BSCs. Direct link between nutrient change, species turn-over and development level in BSCs. IBSC accelerates BSC development by stabilizing soil and offering species resources. Guide for strategy selection in ecological engineering for desertification reversal.